2017
DOI: 10.1038/ncomms14703
|View full text |Cite
|
Sign up to set email alerts
|

Oriented graphene nanoribbons embedded in hexagonal boron nitride trenches

Abstract: Graphene nanoribbons (GNRs) are ultra-narrow strips of graphene that have the potential to be used in high-performance graphene-based semiconductor electronics. However, controlled growth of GNRs on dielectric substrates remains a challenge. Here, we report the successful growth of GNRs directly on hexagonal boron nitride substrates with smooth edges and controllable widths using chemical vapour deposition. The approach is based on a type of template growth that allows for the in-plane epitaxy of mono-layered … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 35 publications
0
86
0
Order By: Relevance
“…Extensive research has shown the outstanding performance of multilayer h-BN as a substrate in electronic devices made from 2D materials 1,4 . Therefore, the fabrication of high-quality h-BN over a large area provides promise for its application in 2D electronics and optoelectronics [6][7][8][9] .…”
mentioning
confidence: 99%
“…Extensive research has shown the outstanding performance of multilayer h-BN as a substrate in electronic devices made from 2D materials 1,4 . Therefore, the fabrication of high-quality h-BN over a large area provides promise for its application in 2D electronics and optoelectronics [6][7][8][9] .…”
mentioning
confidence: 99%
“…However, these ribbons had rough edges which limit carrier transport and thus the usability of the GNRs in devices. 6,7 Epitaxially grown GNRs on SiC show ballistic transport 8 , and GNRs were prepared inside etched trenches in hexagonal boron nitride (hBN) 9 , but both methods again lack atomic precision. Advances in solution chemistry opened up new routes to obtain GNRs by atomically precise bottom-up synthesis.…”
mentioning
confidence: 99%
“…Otherwise, if the AR probability changes a little in the whole energy interval, then it is difficult to draw the key mechanism for the AR suppression. For experimental realization of our proposal, we note that the state of the art of the graphene engineering strongly shows the potential to construct the BPC valley filter in the near future [51][52][53][54][55][56], and recent progress on specular AR in graphene has also confirmed the superconducting proximity effect in graphene [57]. Therefore, it is reasonable to anticipate the realization of our proposal.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…This can be denoted by b L = Ra L , where the final reflection matrix R can be obtained by combining s 1 and s 2 , resulting in [56] …”
Section: Scattering Matrix Analysis Of Andreev Reflectionmentioning
confidence: 99%